Environmental behaviours in initial professional development and their relationship with university education. (1st December 2015) - Fernández-Manzanal, Rosario; Serra, Luis M.; Morales, María J.; Carrasquer, José; Rodríguez-Barreiro, Luis M.; del Valle, Javier; Murillo, María B.
Abstract: This research explores whether university education provides young graduates studying subjects related to the environment with relevant knowledge and strategies for sustainability actions that they can put into practice in the workplace. It also reveals the difficulties and obstacles that graduates encounter in their professional careers to promote pro-environmental strategies in their companies or to maintain sustainable behaviours. Information for the qualitative research was obtained from semi-structured interviews with 70 graduates from eight assorted faculties spread across three campuses at the University of Zaragoza. The paper categorises the most widely detected barriers impeding the application of pro-environmental strategies in the workplace and considers whether these barriers are connected with university education. One of the most relevant conclusions is that a small number of graduates were involved in pro-environmental strategies and only when such strategies were promoted and developed by the firm itself. In these cases the graduates felt that they had been well prepared at the University. However, the majority had not participated in pro-environmental strategies and felt that their university education did not equip them properly for their involvement in environmental projects. This barrier is thus considered a very significant one. A previous research study developed with the same graduates tested a causal model that explained environmental attitudes and their connection with environmental behaviour. In the model, the intention or willingness to act came between attitudes and behaviours. In this work, the unwillingness to act is also shown to be a significant barrier to participating in pro-environmental strategies. As a conclusion, changes are suggested in the curriculum to include core competencies in sustainability in all degrees. It is also proposed that firms and universities establish organisational structures to promote effective sustainability and pro-environmental actions. Highlights: Participation of graduates in environmental strategies in the workplace is analysed. The relationship between university education and professional success is discussed. Qualitative research has been conducted based on semi-structured interviews. Barriers detected by graduates to environmental action in companies are described. This work complements quantitative research published by the same authors.